Extreme food : what to eat when your life depends on it - Grylls, Bear (William Morrow, an imprint of HarperCollinsPublishers, 2015)
This book teaches readers how to forage and prepare simple food in the wild. It also shows how to stalk, hunt and cook game, as well as advice on eating insects, anthropods and amphibians.